An Algorithm for Constructing Reduced DNFs of Order-Convex Boolean Functions - Timoshkin, A. I. (Cybernetics and systems analysis, 2019)
This paper considers the problem of constructing reduced disjunctive normal forms of order-convex Boolean functions. An original algorithm is proposed for finding these forms. The algorithm uses concepts of the theory of ordered sets such as an ideal and a coideal and has a substantially lower time complexity than the classical Quine–McCluskey algorithm.